Evaluating Airport Passenger Terminal Service: Type A Standards - Dian Ardhiya Ekawati; Langas Denny Siahaan; Susanty Handayani (Institut Transportasi dan Logistik Trisakti, 2021)
Terminal is a major node in a network which are collections of the overall trajectory. But now the existence of a passenger terminal does not function effectively, it is seen from the low utilization by the user terminal transport services. Hence, the aim in this study was to evaluate airport terminal service against type A standards. This study was conducted at the Passenger Terminal Type A Tirtonadi Surakarta using descriptive and quantitative research methods, with a sample size of 355 people. Data were collected through an instrument in the form of sheets of questions with Likert scale models that have been tested. The study used the analytical techniques Importance Performance Analysis. Results of the first study, it was concluded that the quality of service in Terminal Tirtonadi ie 81.41 are on service quality category B with satisfactorily. Second, the level of conformity Terminal services Tirtonadi not met the expectations of service users. Thirdly, it was concluded that the services are a top priority for improvement is the safety information that is easy and clear, the Internet network facilities, battery charging facilities, waiting room, and the arrival and departure of vehicles as well as the tariffs of public vehicles.